Addressing the Impact of COVID-19 on the Residency Application Process Through a Virtual Subinternship. (November 2020) - Farlow, Janice L.; Marchiano, Emily J.; Fischer, Ilana P.; Moyer, Jeffrey S.; Thorne, Marc C.; Bohm, Lauren A.
Senior medical students are facing an unparalleled experiential gap left by COVID-19 restrictions. Due to a shared commitment to safety, equity, and well-being, away rotations are actively being discouraged or even prohibited. As a result, students transitioning to residency encounter reduced clinical training experiences and decreased access to advising, mentorship, and research opportunities. In addition, limited exposure to residency life across subspecialties and institutions poses unique challenges during the current residency application cycle. The otolaryngology–head and neck surgery community has met these unprecedented challenges by producing diverse electronic resources for specialty-specific clinical education, as well as discussing ways to increase access to advising. In this commentary, we review these initiatives and propose an institutional virtual event as a platform for meeting goals previously achieved by visiting subinternships.